Pindar in Sicily - Reid, Heather L. (Heritage of Western Greece, 2021)
Even a cursory look at the remaining corpus of Pindar's victory odes leaves one in no doubt about the wealth, power, and prestige of his Sicilian patrons. Exactly a third of the odes were composed for Sicilian athletic victories, all but three in the more illustrious of the four Panhellenic contests (Olympian and Pythian), and almost all of them for single horse or chariot races, which required significantly more expenditure than any of the other athletic competitions. The odes to the ruling families of Deinomeniadai and Emmenidai (Hieron of Syracuse and Theron and Xenokrates of Akragas) are the most numerous and have long been considered among the most beautiful, sophisticated, and memorable ancient Greek poetry. It is thus not surprising that recent scholarship has focused on Pindar's special relationship with Sicily in the context of Sicilian social, political, and cultural climate in the fifth century BCE. On the other hand, surprisingly few scholars of Pindar and the historical context in which he worked have ever been to Sicily to see the hometowns of Pindar's patrons, where the songs would most likely have premiered in elaborate public performances, and which figure prominently in all of his compositions. This volume is the result of bringing scholars from a variety of disciplines to Siracusa to discuss these odes and to visit the archaeological remains of the places and people they celebrate.